Materialism at University students - Saad, Huda; Al-Daqhstani, Sana (Al-Adab Journal, 2023)
Materialism is regarded as a complex phenomenon arises from the interaction among the individual, social and cultural aspects, as well as the social, political and economic changes. The family is also considered the most important factor in socialization by which a person's values and beliefs are formed, and the impact of the peers on the young people to learn about material interests is also an important factor. Poverty and family disintegration contribute to the lack of human feelings, such as love and affection, which cause many individuals to be transformed into materialists. the current research sample of (400) male and female students :(200) male and (200) female. they were randomly chosen from eight colleges, and to achieve the goals of the current research, the researcher adopted the Belk's Trait Theory of Materialism (1984-1985). the reliability coefficient of materialism scale is (0,74). The current research reached the following conclusion: 1- University students display low materialism. 2- there are no difference in materialism among university students according to the gender and the specialization, since there are no significant differences among university students according to gender and specialization, because the calculated Aloha value of (3.49) is smaller the Alpha tabular value of (3,84) on level (0.05) and degree of freedom (396-1). The researcher suggested several proposals, including: 1- Conducting a study similar to the current one deals with different age groups, such as teenagers, children, and employees. 2- Conducting a research bout the materialism and its relationship with consuming compulsive purchase.